Infection with Leishmania (Leishmania) infantum Changes the Morphology and Myenteric Neurons of the Jejunum of Golden Hamsters - de Lima, Sarah Kymberly Santos [UNESP]; Cavallone, Italo Novais [UNESP]; Oliveira, Karine Soares [UNESP]; Passero, Luiz Felipe Domingues [UNESP]; Laurenti, Márcia Dalastra; Jesus, Jéssica Adriana; Marinsek, Gabriela Pustiglione [UNESP]; Chucri, Thaís Martins [UNESP]; Mari, Renata de Britto [UNESP] (MDPI, 2021)
Visceral leishmaniasis (VL) is one of the most severe clinical manifestations of leishmaniasis as it leads to death in 90% of untreated cases. The liver, spleen and bone marrows are the organs most affected; however, Leishmania parasites are able to reach the intestines where the gut-associated lymphoid tissue (GALT) is located. Under physiological conditions, the gastrointestinal tract and GALT interact with the enteric nervous system (SNE); however, there are no studies exploring the modulatory role of Leishmania (Leishmania) infantum in the intestines. Thus, this work aimed to investigate the parasitism, stratigraphy, and morphological changes in the myenteric plexus of golden hamsters infected with L. (L.) infantum. The animals were infected intraperitoneally, and the parasite load was evaluated in the spleen, the liver, and the jejunum. The stratigraphic evaluation and the quantitative and morphometric analyses of NADH-dp and NADPH-dp myenteric neurons were studied at 30-, 60-, and 90-days post-infection (DPI). Parasites in the spleen, the liver, and the jejunum increased during the progression of the infection. Stratigraphy studies showed a significant hypertrophy of the villi and the crypts associated with the increased intraepithelial lymphocytes that were observed in the jejunum of the infected animals. In addition, mucosal atrophy associated with a reduction in AB+ and PAS+ goblet cells was observed at 60 DPI and 90 DPI. These morphological changes were associated with an atrophy of the cell profile from NADPH-dp myenteric neurons. Furthermore, a significant decrease in the densities of this neuron population was observed in the chronic phase of the infection. This study suggests that L. (L.) infantum parasites are able to alter the morphology and innervation of the jejunum in golden hamsters.
Keywords: inflammation; intestinal barrier; NADH-dp; NAPH-dp; visceral leishmaniasis